Implementation of Students’ Worksheets to Improve Critical Thinking Skills (Jurnal Pendidikan Fisika, 2022)
This study aims to (1) provide an overview of the critical thinking skills of students at SMAN 3 Enrekang, (2) to analyse the improvement of students critical thinking skills using the environment based students’ worksheets at SMAN 3 Enrekang (3) to analyse the improvement of students’ critical thinking skills using the conventional students’ worksheets at SMAN 3 Enrekang (4) to compare the use of environment-based students’ worksheets and conventional ones. The research is a quasi-experimental study. The independent variable is the learning model and the dependent variable is the critical thinking skills of students in learning physics. The population in this study were all students of class XI MIPA. Taken by using purposive sampling technique, class of XI MIPA I was the experimental class and XI MIPA II was the control class. Based on descriptive statistical analysis, it was found that (1) the average pretest and post-test scores of critical thinking skills in the experimental class are both in the high category, while the pretest and post-test scores in the control class was the sufficient category and the high category, respectively (2) there is an increase in students’ critical thinking skills in using an environment based students’ worksheets strategy at SMAN 3 Enrekang, (3) there is an increase in students’ critical thinking skills using conventional students’ worksheets, (4) there are differences in the use of environment based student worksheets where the  obtained is 0,15 smaller than α 0,05. These results indicate that there are differences in critical thinking skills of students of SMAN 3 Enrekang when using environmental-based student worksheets and without using environmental-based student worksheets.
Keywords: critical thinking skills; environment; learning strategies